Multifunctional nanocomposites based on metal-organic frameworks and methods of making and using the same

CN122937247APending Publication Date: 2026-10-20LULIANG PEOPLES HOSPITAL (LÜLIANG HOSPITAL AFFILIATED TO SHANXI MEDICAL UNIV ELEVENTH CLINICAL COLLEGE OF SHANXI MEDICAL UNIV)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611263403.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有MOF载体多局限于单一功能,如仅用于药物递送,缺乏对RA复杂病理微环境的主动响应和多重调控能力

Benefits of technology

[0017]本发明以铜锌双金属有机框架为基底,利用其高比表面积和孔道结构共负载软骨修复药物Kartogenin;通过在其表面修饰透明质酸-阿仑膦酸钠偶合物,赋予纳米粒主动靶向软骨及CD44阳性细胞的能力,同时增强其生物相容性和关节润滑潜力。该纳米复合物在模拟炎症微环境的弱酸性条件下可实现药物的响应性释放,其类过氧化物酶活性可清除活性氧。细胞实验表明,该纳米复合物能有效清除细胞内活性氧,抑制炎症因子释放,促进软骨细胞迁移,其抗炎机制与抑制NF-κB信号通路相关。动物实验验证,该纳米复合物可在类风湿关节炎小鼠关节部位有效滞留,显著缓解关节肿胀与僵直,保护关节软骨,且主要脏器未见明显病理损伤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a multifunctional nanocomposite based on a metal-organic framework, its preparation method, and its applications. The multifunctional nanocomposite comprises a drug-carrier, a cartilage repair drug, and a targeting modifier. The drug-carrier is a copper-zinc bimetallic organic framework, formed by the coordination of zinc ions, copper ions, and 2-methylimidazole. The cartilage repair drug is loaded onto the drug-carrier to form drug-loaded nanoparticles. The targeting modifier is a hyaluronic acid-alendronate sodium conjugate, modified on the surface of the drug-loaded nanoparticles. This invention uses a copper-zinc bimetallic organic framework as a substrate, utilizing its high specific surface area and porous structure to co-load cartilage repair drugs. By modifying its surface with a hyaluronic acid-alendronate sodium conjugate, the nanoparticles are endowed with the ability to actively target cartilage and CD44-positive cells. This nanocomposite can target and deliver drugs to inflamed joints, respond to drug release in an acidic microenvironment, exhibit antioxidant and anti-inflammatory properties, inhibit osteoclast activity, and promote chondrocyte differentiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomedicine delivery system preparation technology, and more specifically, to a multifunctional nanocomposite based on a metal-organic framework, its preparation method, and its application. Background Technology

[0002] Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic synovitis. Its progressive course leads to articular cartilage erosion, bone destruction, and functional impairment, severely threatening patients' quality of life. The pathogenesis of RA involves a complex interaction of genetic susceptibility, environmental factors, and immune dysregulation. The body's immune tolerance to self-antigens is disrupted, resulting in extensive infiltration of inflammatory cells and the release of pro-inflammatory factors (TNF-α, IL-1β, IL-6).

[0003] Currently, while antirheumatic drugs (ART) have significantly improved the clinical prognosis of RA patients, their treatment still faces many limitations. Methotrexate, as a first-line drug, suffers from significant individual variability in response, slow onset of action, and is often accompanied by adverse reactions such as gastrointestinal upset and hepatotoxicity. Although biological antirheumatic drugs can target key inflammatory mediators such as TNF-α or IL-6, their high cost, the need for injection administration, and the potential for increased serious infection risk with long-term use limit their widespread application. Therefore, developing novel treatment strategies that combine precise targeting, high efficacy, low toxicity, and long-acting sustained-release properties remains a crucial scientific challenge in the field of RA treatment.

[0004] The rise of nanomedicine delivery systems has provided a new technological pathway for the treatment of rheumatoid arthritis (RA). However, traditional nanocarriers generally suffer from drawbacks in in vivo applications, such as short circulating half-life, poor stability, easy drug dilution, and lack of lesion-specific targeting ability. These limitations make it difficult for drugs to be effectively accumulated at inflamed joint sites and maintain a sustained therapeutic effect. An ideal RA therapeutic carrier should possess high drug loading capacity, biodegradability, stimulus-responsive release capability, and the ability to actively target diseased tissue.

[0005] Metal-organic frameworks (MOFs) have shown great promise in drug delivery due to their high specific surface area, tunable pore structure, and ease of surface modification. However, existing MOF carriers are mostly limited to a single function, such as drug delivery, and lack the ability to actively respond to and regulate the complex pathological microenvironment of rheumatoid arthritis (RA). Summary of the Invention

[0006] The purpose of this invention is to provide a multifunctional nanocomposite based on a metal-organic framework, its preparation method and application. This nanocomposite can target and deliver inflamed joints, respond to drug release in an acidic microenvironment, and has antioxidant, anti-inflammatory, and osteoclast-inhibiting and chondrocyte-promoting effects.

[0007] To achieve the above objectives, according to one aspect of the present invention, a multifunctional nanocomposite based on a metal-organic framework is provided, comprising a drug carrier, a cartilage repair drug, and a targeted modifier; The drug delivery carrier is a copper-zinc bimetallic organic framework, which is formed by the coordination of zinc ions, copper ions and 2-methylimidazole. The cartilage repair drug is loaded onto a drug-carrying carrier to form drug-loaded nanoparticles; The targeted modifier is a hyaluronic acid-alendronate sodium conjugate, which is modified on the surface of drug-loaded nanoparticles.

[0008] In a preferred embodiment, the molar ratio of zinc ions to copper ions in the copper-zinc bimetallic organic framework is 1:0.5~1.5.

[0009] In a preferred embodiment, the cartilage repair drug is Kartogenin.

[0010] According to another aspect of the present invention, a method for preparing the above-described metal-organic framework-based multifunctional nanocomposite is provided, comprising: Step 1: Mix a methanol solution containing zinc salt and copper salt with a methanol solution containing 2-methylimidazole and react under stirring at room temperature to obtain a copper-zinc bimetallic organic framework. Step 2: Disperse the copper-zinc bimetallic organic framework and cartilage repair drugs in ethanol and react them under stirring conditions at room temperature to obtain drug-loaded nanoparticles. Step 3: The drug-loaded nanoparticles and the hyaluronic acid-alendronate sodium conjugate are dispersed in a buffer solution and reacted under stirring conditions at room temperature to obtain the aforementioned multifunctional nanocomposite based on a metal-organic framework.

[0011] In a preferred embodiment, in step one, the zinc salt is zinc nitrate and the copper salt is copper nitrate.

[0012] In a preferred embodiment, in step two, the mass ratio of the copper-zinc bimetallic organic framework to the cartilage repair drug is 3-5:1.

[0013] In a preferred embodiment, step three involves preparing the hyaluronic acid-alendronate sodium conjugate by adding hyaluronic acid to an aqueous solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide for activation, then adding alendronate sodium for amidation reaction, followed by purification and drying to obtain the hyaluronic acid-alendronate sodium conjugate.

[0014] As a preferred embodiment, the mass ratio of hyaluronic acid to sodium alendronate is 1:2.

[0015] In a preferred embodiment, in step three, the mass ratio of the drug-loaded nanoparticles to the hyaluronic acid-alendronate sodium conjugate is 2:1.

[0016] According to another aspect of the invention, the use of the aforementioned metal-organic framework-based multifunctional nanocomposite in the preparation of a medicament for treating rheumatoid arthritis is provided.

[0017] This invention utilizes a copper-zinc bimetallic organic framework as a substrate, leveraging its high specific surface area and porous structure to co-load the cartilage repair drug Kartogenin. By modifying its surface with a hyaluronic acid-alendronate sodium conjugate, the nanoparticles are endowed with the ability to actively target cartilage and CD44-positive cells, while simultaneously enhancing their biocompatibility and joint lubrication potential. This nanocomposite achieves responsive drug release under weakly acidic conditions simulating an inflammatory microenvironment, and its peroxidase-like activity scavenges reactive oxygen species (ROS). Cellular experiments demonstrate that this nanocomposite effectively scavenges intracellular ROS, inhibits the release of inflammatory factors, and promotes chondrocyte migration; its anti-inflammatory mechanism is related to the inhibition of the NF-κB signaling pathway. Animal experiments validate that this nanocomposite can effectively remain in the joints of mice with rheumatoid arthritis, significantly alleviating joint swelling and stiffness, protecting articular cartilage, and without significant pathological damage to major organs.

[0018] The nanocomposite provided by this invention integrates targeted delivery, microenvironment-responsive drug release, antioxidant, anti-inflammatory and chondrocyte differentiation promotion functions, providing a new strategy for the integrated diagnosis and treatment of rheumatoid arthritis. Attached Figure Description

[0019] Figure 1 Transmission electron microscope (TEM) images of KDM and KDM@HAN provided in Example 1. (a) and (b) are morphological images of KDM at different magnifications, respectively; (c) is a morphological image of KDM@HAN. Figure 2 The X-ray photoelectron spectroscopy (XPS) results of the KDM@HAN provided in Example 1 are shown. (a) is the overall spectrum; (b) is the Cu 2p high-resolution spectrum; (c) is the Zn 2p high-resolution spectrum; and (d) is the P 2p high-resolution spectrum. Figure 3 The drug release curves of KDM@HAN provided in Example 1 under different pH conditions are shown. (a) shows the in vitro cumulative release curves of KDM and KDM@HAN under weakly acidic conditions (pH 5.5); (b) shows the in vitro cumulative release curves of KDM and KDM@HAN under neutral conditions (pH 7.4). Figure 4The images show the cell uptake results of KDM@HAN provided in Example 1. (a) is a fluorescence image of RAW 264.7 cells; (b) is a quantitative analysis of the mean fluorescence intensity of RAW 264.7 cells; (c) is a fluorescence image of ATDC-5 cells; and (d) is a quantitative analysis of the mean fluorescence intensity of ATDC-5 cells. Data are expressed as mean ± standard deviation. *p < 0.05, **p < 0.01, and ***p < 0.001 Figure 5 The figures show the results of KDM@HAN's effect on intracellular reactive oxygen species scavenging provided in Example 1. (a) and (b) are fluorescence images and quantitative analysis of mean fluorescence intensity of RAW 264.7 cells, respectively; (c) and (d) are fluorescence images and quantitative analysis of mean fluorescence intensity of ATDC-5 cells, respectively. Data are expressed as mean ± standard deviation. *p < 0.05, **p < 0.01 and ***p < 0.001 Figure 6 The results of the effect of KDM@HAN on cell migration ability provided in Example 1 are shown in the figure. (a) Scratch healing images of each group at 0, 12, and 24 h; (b) Quantitative analysis of migration rate at different time points for each group. Data are expressed as mean ± standard deviation. *p < 0.05, **p < 0.01, and ***p < 0.001 Figure 7 The graph shows the results of the inhibitory effect of KDM@HAN on inflammatory factors provided in Example 1. (a) IL-6; (b) IL-1β; (c) TNF-α; (d) MMP-13; Figure 8 The therapeutic effect of KDM@HAN provided in Example 1 on a mouse model of rheumatoid arthritis is shown in the figures. (a) Representative photographs of the metacarpophalangeal joint of the right hind limb of mice in each group on days 10, 18, and 28 (red arrows indicate swollen areas, blue arrows indicate stiff areas); (b) Dynamic curves showing the percentage increase in the thickness of the right hind limb paw in each group of mice. Data are expressed as mean ± standard deviation. *p < 0.05, **p < 0.01, and ***p < 0.001 Figure 9 In vivo imaging of the retention capacity of KDM@HAN at the joint site provided in Example 1. (a) In vivo fluorescence imaging of each group of materials at different time points after drug administration; (b) Relative quantitative analysis curve of fluorescence intensity in the joint region. Detailed Implementation

[0020] A typical embodiment of the present invention provides a multifunctional nanocomposite based on a metal-organic framework, comprising a drug carrier, a cartilage repair drug, and a targeted modifier.

[0021] The drug carrier is a copper-zinc bimetallic organic framework, formed by the coordination of zinc ions, copper ions and 2-methylimidazole, which can efficiently load chondrogenic drugs.

[0022] In the copper-zinc bimetallic organic framework, the molar ratio of zinc ions to copper ions is 1:0.5~1.5, for example, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, etc.

[0023] The cartilage repair drug is loaded onto a drug-carrying carrier to form drug-loaded nanoparticles; the cartilage repair drug is Kartogenin (KGN).

[0024] The targeted modifier is a hyaluronic acid-alendronate sodium conjugate, which is modified on the surface of drug-loaded nanoparticles.

[0025] The copper-zinc bimetallic organic framework (Cu / Zn-MOF) provided in this embodiment not only achieves high drug loading rates that are difficult to reach with traditional carriers, but the characteristics of the coordination bonds in its structure also endow it with degradable properties under specific physiological conditions (such as a weakly acidic microenvironment), thereby enabling stimulus-responsive drug release. Furthermore, Cu / Zn-MOF and its derivatives may possess inherent anti-inflammatory or antioxidant activities, providing the potential for a multifunctional therapeutic platform for the intervention of inflammatory diseases.

[0026] Hyaluronic acid (HA) is a natural high-molecular-weight linear polysaccharide that specifically binds to the CD44 receptor, which is highly expressed on the surface of inflammatory synovial cells (especially activated macrophages) in rheumatoid arthritis (RA). Therefore, it is widely used as a targeting ligand in nanodelivery systems. Studies have shown that HA-modified nanoparticles not only prolong drug retention time at joint sites but also promote drug delivery to target cells through receptor-mediated endocytosis, thereby improving therapeutic efficacy. Simultaneously, HA's excellent biocompatibility and lubricating properties enable it to exert a synergistic protective effect at inflamed joint sites.

[0027] Alendronate sodium (ALN), a bisphosphonate drug, has a high affinity for hydroxyapatite in bone tissue and can specifically bind to areas of active bone remodeling. During rheumatoid arthritis (RA), the subchondral bone and bone erosion sites exhibit abnormally active bone metabolism, providing ideal binding sites for ALN. Modifying ALN onto the surface of a nanocarrier endows it with the ability to actively target bone erosion sites, promoting drug accumulation in the bone-damaging area. Furthermore, ALN itself inhibits osteoclast activity and reduces bone resorption, exhibiting a synergistic effect when used in combination with cartilage repair drugs.

[0028] By modifying the surface of the hyaluronic acid-alendronate sodium conjugate, the drug delivery system can achieve synergistic effects of cartilage differentiation-promoting drug therapy and anti-inflammatory and antioxidant therapy, improve targeting efficiency, enhance penetration depth, prolong drug release, and thus delay the progression of rheumatoid arthritis.

[0029] Another typical embodiment of the present invention provides a method for preparing the above-described multifunctional nanocomposite based on a metal-organic framework, comprising the following steps one to three.

[0030] Step 1: Preparation of copper-zinc bimetallic organic framework (Cu / Zn-MOF) A methanol solution containing zinc and copper salts was mixed with a methanol solution containing 2-methylimidazole and reacted under stirring at room temperature to obtain a copper-zinc bimetallic organic framework.

[0031] The zinc salt is zinc nitrate, and the copper salt is copper nitrate.

[0032] Step 2: Preparation of drug-loaded nanoparticles (KGN / Cu / Zn-MOF, abbreviated as KDM) A copper-zinc bimetallic organic framework and a cartilage repair drug were dispersed in ethanol and reacted under stirring conditions at room temperature to obtain drug-loaded nanoparticles KDM.

[0033] The mass ratio of the copper-zinc bimetallic organic framework to the cartilage repair drug is 3 to 5:1. For example, the mass ratio of the copper-zinc bimetallic organic framework to the cartilage repair drug is 3:1, 4:1 or 5:1, etc.

[0034] Step 3: Preparation of multifunctional nanocomposites based on metal-organic frameworks (KDM@HAN) Drug-loaded nanoparticles and hyaluronic acid-alendronate sodium conjugate (HAN) were dispersed in a buffer solution and reacted under stirring at room temperature to obtain the aforementioned metal-organic framework-based multifunctional nanocomposite (KDM@HAN).

[0035] The preparation method of the hyaluronic acid-alendronate sodium conjugate (HAN) includes: activating hyaluronic acid by adding it to an aqueous solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, then adding alendronate sodium for amidation reaction, and finally purifying and drying to obtain the hyaluronic acid-alendronate sodium conjugate. The preferred mass ratio of hyaluronic acid to alendronate sodium is 1:2.

[0036] The preferred mass ratio of drug-loaded nanoparticles to the hyaluronic acid-alendronate sodium conjugate is 2:1. The reaction time between the drug-loaded nanoparticles and the hyaluronic acid-alendronate sodium conjugate is 10 h to 14 h, for example, 10 h, 11 h, 12 h, 13 h or 14 h.

[0037] The technical solutions claimed in this invention will be further described below through some relatively specific embodiments. However, the embodiments are used to explain the implementation schemes of this invention and do not exceed the scope of the subject matter of this invention. The scope of protection of this invention is not limited by the embodiments described. Unless otherwise specified, the materials and reagents used in this invention can be obtained from commercially available products in the art.

[0038] Example 1: Preparation of a multifunctional nanocomposite based on a metal-organic framework (KDM@HAN) (1) Preparation of copper-zinc bimetallic organic framework (Cu / Zn-MOF) A homogeneous methanol solution containing 3.352 g Zn(NO3)2·6H2O and 0.143 g Cu(NO3)2·3H2O was reacted with 120 mL of a methanol solution containing 3.888 g 2-methylimidazole at room temperature under magnetic stirring (approximately 450 rpm) for 4 hours. The precipitate was collected, washed three times with ethanol, and dried under vacuum at 60°C to obtain Zn. 2+ With Cu 2+ A copper-zinc bimetallic organic framework (Cu / Zn-MOF) with a molar ratio of 1:1.

[0039] (2) Preparation of hyaluronic acid-alendronate sodium conjugate (HAN) Add 800 mg of EDC and 400 mg of NHS to a 200 mL beaker, add 60 mL of deionized water, and dissolve by magnetic stirring. Weigh 200 mg of hyaluronic acid and add it to the above solution. Stir magnetically at room temperature for 1 hour to activate the carboxyl groups on the HA molecules. Then, weigh 400 mg of sodium alendronate (ALN) and add it to the reaction system, and continue stirring at room temperature for 24 hours. Transfer the reaction solution to a dialysis bag (MWCO 3500 Da) and dialyze with purified water for 48 hours, changing the dialysate every 4-6 hours to remove unreacted small molecule impurities. After dialysis, freeze-dry the liquid in the bag to obtain a white flocculent solid HAN, which is stored at 4°C for later use.

[0040] (3) Preparation of drug-loaded nanoparticles (KDM) Weigh 10 mg of Cu / Zn-MOF prepared in step (1) and disperse it in 5 mL of anhydrous ethanol. Add KGN ethanol solution (2 mg / mL, 1 mL) and stir at room temperature in the dark for 24 h. Centrifuge (10000 rpm, 10 min) to collect the precipitate, wash it three times with anhydrous ethanol to obtain drug-loaded nanoparticles (KDM), dry them under vacuum and store them at 4°C in the dark.

[0041] (4) Preparation of nanocomposite (KDM@HAN) Weigh 10 mg of KDM and disperse it in 10 mL of phosphate buffer (PBS, pH 7.4). Add 5 mg of HAN prepared in step (2) and stir at room temperature for 12 h. Centrifuge (12000 rpm, 15 min) to remove unbound HAN and wash twice with PBS to obtain the nanocomposite KDM@HAN.

[0042] Analysis of transmission electron microscopy results of KDM and KDM@HAN Transmission electron microscopy was performed on the KDM and KDM@HAN obtained in Example 1, and the results are as follows: Figure 1 As shown, KDM nanoparticles exhibit a regular and uniform hexahedral morphology with a particle size of approximately 200 nm; the particle size of the KDM@HAN nanocomposite is slightly increased, and a distinct low-density coating layer can be observed, indicating that HA-ALN has been successfully modified onto the KDM surface.

[0043] Analysis of X-ray photoelectron spectroscopy results of KDM@HAN X-ray photoelectron spectroscopy analysis was performed on the KDM@HAN obtained in Example 1. The results are as follows: Figure 2 As shown, the overall spectrum mainly contains elements such as Cu, Zn, F, P, C, and O, confirming the successful introduction of various functional components into the material. In the Cu2p high-resolution spectrum, the peaks at 932.6 eV and 952.4 eV confirm that Cu is present primarily as Cu. 2+ It exists in Zn2p form. In the Zn2p spectrum, the peaks at 1021.8 eV and 1044.9 eV indicate that Zn exists in Zn2p form. 2+ The form exists. In the F1s high-resolution spectrum, the peak at 684.9 eV belongs to the CF bond in KGN, proving that KGN was successfully loaded. In the P2p spectrum, the peak at 133.2 eV corresponds to the PO bond in ALN, confirming that ALN was successfully modified on the material surface by HA-ALN.

[0044] Investigating the drug release behavior of KDM and KDM@HAN under different pH conditions. The in vitro drug release behavior of KDM and KDM@HAN under different pH conditions was determined by dialysis. The release media were phosphate-buffered saline (PBS) at pH 7.4 and pH 5.5, respectively simulating the physiological environment and the inflammatory microenvironment of rheumatoid arthritis. Both media contained 0.5% (v / v) Tween-80 to maintain the leak conditions. Lyophilized KDM and KDM@HAN powders were ultrasonically dispersed in the corresponding release media to prepare dispersions of 2 mg / mL. Dialysis bags with a molecular weight cutoff of 3500 Da were pretreated and used. The experiment was divided into four groups: KDM (pH 7.4), KDM (pH 5.5), KDM@HAN (pH 7.4), and KDM@HAN (pH 5.5), with three replicates in each group. 1 mL of the above dispersion was placed in a dialysis bag, sealed, and immersed in 50 mL of the corresponding release medium. Release was carried out by shaking at 37℃ and 100 rpm in the dark. At preset time points, 2 mL of the release solution was collected and replenished with an equal volume of fresh medium at the same temperature and pH. After appropriate dilution of the collected release solution, the absorbance was measured at the maximum absorption wavelength of KGN. The drug concentration was calculated based on the standard curve. The cumulative release rate at each time point was calculated using the formula "Release rate (%) = Release amount / Drug loading × 100%", and the release curve was plotted.

[0045] The cumulative release curves of each group of drugs are as follows: Figure 3 As shown, under weakly acidic conditions (pH 5.5) simulating an inflammatory microenvironment, unencapsulated KDM exhibited rapid release within 10 h, with a cumulative release rate of 91.45%, indicating that the MOF carrier rapidly disintegrates under acidic conditions, leading to rapid drug release. However, the release rate of KDM@HAN encapsulated with HAN was significantly slowed, with a release period extended to approximately 80 h and a cumulative release rate of 81.74%, indicating that the outer HAN shell effectively delays the diffusion and release of the internal drug. Under neutral conditions (pH 7.4) simulating a physiological environment, KDM also exhibited rapid initial release behavior, but the release rate was slightly slower than under pH 5.5 conditions; the release rate of KDM@HAN under neutral conditions was also significantly lower than that of unencapsulated KDM, with a significantly prolonged release period. The above results indicate that the KDM@HAN nanocomposite possesses dual release characteristics: on the one hand, it can achieve rapid responsive release under the weakly acidic conditions of the inflammatory microenvironment, which is beneficial for quickly reaching an effective therapeutic concentration at the lesion site; on the other hand, the encapsulation effect of the outer HAN layer can effectively delay drug release, achieving a long-lasting sustained-release effect, which is beneficial for improving therapeutic efficacy and reducing the frequency of drug administration.

[0046] Examined the uptake capacity of KDM and KDM@HAN by RAW 264.7 macrophages and ATDC-5 chondrocytes. Confocal laser scanning microscopy combined with flow cytometry was used to evaluate the uptake behavior of RAW 264.7 macrophages and ATDC-5 chondrocytes on rhodamine B-labeled KDM and KDM@HAN. Cells were cultured at a rate of 1×10⁻⁶ cells / cells. 5 Cells were seeded at a density of 1 cell / well in confocal culture dishes and cultured for 24 h. Afterward, Rhodamine B-labeled KDM or KDM@HAN (40 μg / mL) was added, and the cells were incubated in the dark for 1, 2, and 4 h. The reaction was terminated by washing three times with pre-cooled PBS, and the cells were fixed with 4% paraformaldehyde for 15 min. After nuclei staining with DAPI, the cells were observed under a confocal microscope (excitation wavelengths of 561 nm and 405 nm). Image acquisition was performed, and the average fluorescence intensity was quantified using ImageJ software. Simultaneously, cells were seeded at a density of 2 × 10⁶ cells / well. 5 Cells were seeded per well in 12-well plates, treated as described above, digested and collected, filtered through a 200-mesh nylon mesh, and their fluorescence intensity in the PE channel was detected by flow cytometry (10,000 cells per sample). The mean fluorescence intensity and percentage of positive cells were analyzed using FlowJo software. Experiments were independently repeated three times, and data are expressed as mean ± standard deviation.

[0047] The uptake of the nanocomposite by cells in each group is as follows: Figure 4 a (RAW 264.7 cells) and Figure 4 As shown in b (ATDC-5 cells), confocal images reveal that the distribution and intensity of red fluorescently labeled nanoparticles within cells reflect their uptake efficiency. In RAW 264.7 cells, the KDM group exhibited moderate-intensity red fluorescence; the KDM@HAN group showed significantly enhanced red fluorescence with a denser distribution. Image J quantitative analysis showed that the average fluorescence intensity of the KDM@HAN group was approximately 2.8 times that of the KDM group, a finding consistent with flow cytometry. Similarly, in ATDC-5 chondrocytes, the red fluorescence intensity in the KDM@HAN group was significantly higher than that in the KDM group. Quantitative results indicated that the average fluorescence intensity of the KDM@HAN group was approximately 2.5 times that of the KDM group, a trend further confirmed by flow cytometry. Time-dependent uptake experiments for both cell types showed that the average fluorescence intensity and the percentage of positive cells in the KDM@HAN group increased with prolonged incubation time, reaching their peak at 4 h. The above results indicate that HAN surface modification can significantly improve the cellular uptake efficiency of nanocomposites. This is due to the specific binding of hyaluronic acid to the CD44 receptor on the cell surface. This advantage lays the foundation for subsequent in vivo targeted delivery and efficacy studies.

[0048] Evaluation of the ability of different materials to scavenge LPS-induced intracellular reactive oxygen species overexpression. The ability of KDM@HAN to scavenge reactive oxygen species (ROS) in LPS-induced RAW 264.7 macrophages and ATDC-5 chondrocytes was assessed using the DCFH-DA fluorescent probe. Cells were inoculated at a rate of 1×10⁻⁶ cells / cells. 5 Seeds were seeded per well in 24-well plates and cultured for 24 h before use. The experiment included a blank control group, an LPS model group, an LPS+NAC positive control group, an LPS+MOF group, an LPS+KDM group, and an LPS+KDM@HAN group. Except for the blank control group, all other groups were pretreated with LPS (1 μg / mL) for 4 h, then incubated with PBS, NAC (5 mM), MOF, KDM, or KDM@HAN (40 μg / mL) for 6 h, respectively. After incubation, the DCFH-DA probe (10 μM) was added and incubated at 37℃ in the dark for 30 min. After washing, the samples were observed under a fluorescence microscope (excitation 488 nm / emission 525 nm), and the average fluorescence intensity of each group was quantitatively analyzed using ImageJ software. Each group had three replicates, and the experiment was independently repeated three times.

[0049] The results are as follows Figure 5 a (RAW 264.7 cells) and Figure 5 b (ATDC-5 cells) shows that in RAW 264.7 cells, only weak fluorescence was observed in the blank control group; the fluorescence of the LPS model group was sharply enhanced, approximately 20 times that of the control group, indicating successful induction of ROS burst. The fluorescence of the MOF and KDM groups was slightly weaker than that of the LPS model group, but the magnitude was limited; the fluorescence intensity of the KDM@HAN group was significantly reduced, only 28% of that of the LPS model group, showing better performance than the MOF and KDM groups. In ATDC-5 cells, the fluorescence of the LPS model group was approximately 18 times that of the control group; the fluorescence of the KDM@HAN group decreased to 31% of that of the LPS model group, significantly better than other material groups. These results indicate that the KDM@HAN nanocomposite can effectively scavenge LPS-induced intracellular ROS overexpression, and its excellent antioxidant capacity may be attributed to the synergistic effect of enhanced cellular uptake by HAN modification and MOF-like peroxidase activity.

[0050] Evaluation of the effect of KDM@HAN nanocomposite on the migration ability of ATDC-5 chondrocytes The effect of KDDM@HAN on the migration ability of ATDC-5 chondrocytes was evaluated using a cell scratch assay. Logarithmic growth phase cells were harvested at 5 × 10⁶ cells / year. 5Each sample was seeded per well in a 6-well plate and cultured for 24 h until confluence reached 90% or higher. A vertical scratch was made using a 200 μL sterile pipette tip, and the sample was gently washed with PBS and photographed immediately at 0 h. The experiment included a control group, MOF group, KGN group, KDM group, and KDM@HAN group, all with a material concentration of 40 μg / mL. After drug addition, the samples were cultured for an extended period, and photographs were taken at 12 h and 24 h. The scratch area was measured using ImageJ software, and the migration rate was calculated using the formula: "Migration rate = (Area at 0 h - Area at that time point) / Area at 0 h × 100%". The experiment was independently repeated three times, and the results are expressed as mean ± standard deviation. Statistical analysis was performed using GraphPad Prism.

[0051] Representative images and quantitative migration results of scratch healing in each group are attached. Figure 6 As shown in the figure. At 0 h post-scratching, the scratch widths in all groups were basically the same. After 12 h of culture, only a small number of cells migrated in the control group and MOF group, with migration rates of 3% and 4%, respectively; the KGN group had more cell coverage in the scratched area, with a migration rate of 18%; the KDM group had a migration rate of 31%; and the KDM@HAN group had mostly healed the scratches, with a migration rate as high as 46%. After 24 h of culture, the scratches in the control group and MOF group were still clearly visible, with migration rates of 5% and 7%, respectively; the KGN group had basically healed the scratches but with a small number of gaps remaining, with a migration rate of 24%; the KDM group had good scratch healing, with a migration rate rising to 42%; and the KDM@HAN group had almost completely healed the scratches, with a migration rate as high as 73%, approximately 1.7 times that of the KDM group and 3.0 times that of the KGN group, significantly better than other groups at each time point (P < 0.01). These results indicate that the KDM@HAN nanocomposite, benefiting from the enhanced cell affinity of HAN modification and the continuous release of KGN, exhibits the best ability to promote chondrocyte migration and recruitment, which is beneficial for in vivo articular cartilage repair.

[0052] Different materials affect the inflammation in LPS-induced RAW 264.7 macrophage and ATDC-5 chondrocyte inflammation models. Effects of factor secretion Enzyme-linked immunosorbent assay (ELISA) was used to evaluate the regulatory effects of KDM@HAN nanocomposite, unmodified KDM, and KGN on the secretion of inflammatory factors in an LPS-induced inflammation model of RAW 264.7 macrophages and ATDC-5 chondrocytes. Logarithmically growing RAW 264.7 macrophages and ATDC-5 chondrocytes were collected and analyzed at a concentration of 2 × 10⁻⁶ cells / cell. 5Cells were seeded at a density of cells / well in 24-well plates and cultured at 37°C in a 5% CO2 incubator for 24 h. After cell attachment, the cells were divided into five groups: control group (normal culture), LPS model group (1 μg / mL LPS), KGN group (40 μg / mL KGN + 1 μg / mL LPS), KDM group (40 μg / mL KDM + 1 μg / mL LPS), and KDM@HAN group (40 μg / mL KDM@HAN + 1 μg / mL LPS). Except for the control group, the other groups were pretreated with LPS (final concentration 1 μg / mL) for 24 h to induce an inflammation model, followed by co-incubation with the corresponding materials for 4 h. The cell supernatant from each well was collected, centrifuged at 3000 rpm for 10 min at 4°C, and the supernatant was stored at -80°C for later use. For the assay, standards and test samples were added to 96-well plates pre-coated with the corresponding antibodies (100 μL / well, 3 replicates) and incubated at 37°C for 90 min. Biotinylated antibody (100 μL / well) was added and incubated at 37°C for 60 min. After washing the plate 5 times, enzyme conjugate (100 μL / well) was added and incubated at 37°C in the dark for 30 min. After washing 5 more times, TMB chromogenic substrate (100 μL / well) was added and incubated at 37°C in the dark for 15–20 min. After terminating the reaction, the OD value was measured at 450 nm. The concentrations of each factor were calculated based on the standard curve, and the results are expressed as mean ± standard deviation. The inflammatory factors detected included IL-6, IL-1β, and TNF-α, which were detected in both cell types. MMP-13, a chondrocyte-specific collagen-degrading enzyme, was detected only in ATDC-5 chondrocytes.

[0053] The expression levels of inflammatory factors and MMP-13 in each group are shown in the attached figure. Figure 7As shown in the figure, in RAW 264.7 macrophages, the levels of IL-6, IL-1β, and TNF-α in the LPS model group were significantly higher than those in the control group (P < 0.001), indicating that the inflammation model was successfully established. Compared with the LPS model group, the KGN group, KDM group, and KDM@HAN group all reduced the secretion levels of the above three inflammatory factors to varying degrees, with the KDM@HAN group showing the most significant inhibitory effect, reducing the levels of IL-6, IL-1β, and TNF-α to 31%, 28%, and 35% of those in the LPS group, respectively. In ATDC-5 chondrocytes, the KDM@HAN group also showed the best inhibitory effect, reducing the levels of IL-6, IL-1β, and TNF-α to 33%, 29%, and 38% of those in the LPS group, respectively. Notably, the expression level of MMP-13 in the KDM@HAN group decreased to 27% of that in the LPS group, which was significantly better than that in the KDM group (reduced to 52% of that in the LPS group) and the KGN group (reduced to 61% of that in the LPS group). The above results indicate that the KDM@HAN nanocomposite can significantly inhibit LPS-induced secretion of inflammatory factors at the protein level and specifically downregulate the expression of MMP-13 in chondrocytes. Its anti-inflammatory and chondrogenic effects are significantly better than those of the unmodified KDM and KGN groups, providing strong in vitro experimental evidence for its application in the treatment of inflammatory joint diseases.

[0054] Evaluating the in vivo anti-RA therapeutic effect of KDM@HAN nanocomposite Using a collagen-induced rheumatoid arthritis (CIA) mouse model, we evaluated the in vivo anti-RA therapeutic effects of KDM@HAN nanocomposite, unmodified KDM, and carrier Cu / Zn-MOF.

[0055] After successful modeling, the model mice were randomly divided into four groups: control group (Ctrl), MOF vector group, KDM group, and KDM@HAN group, with six mice in each group. Age-matched healthy mice without any treatment served as normal controls. Administration was via intra-articular injection into the left hind limb ankle-palmar-plantar joint. The Ctrl group received an equal volume of sterile saline, while the other groups received the corresponding material dispersion (concentration 2 mg / mL, injection volume 20 μL, i.e., 40 μg per mouse per administration). Administration was repeated every two days starting from day 10, for a total of 10 administrations (on days 10, 12, 14, 16, 18, 20, 22, 24, 26, and 28). Throughout the treatment period, the severity of arthritis lesions in the mice was dynamically monitored before each administration. Specific evaluation indicators include: (1) Gross observation and photography: Using a digital camera, take photos of the front of the metatarsophalangeal joint of the right hind limb of the mouse under the same lighting and distance conditions, and record the degree of joint redness, swelling, deformation and stiffness; (2) Toe thickness measurement: Use an electronic vernier caliper to measure the thickness of the paw at the same location. Each mouse is measured three times and the average value is taken. The thickness of the mouse's own paw before modeling is used as the baseline. The percentage increase in thickness is calculated according to the formula "swelling percentage (%) = ((thickness at this time point - thickness before modeling) / thickness before modeling) × 100%"; record all data for statistical analysis. At the end of the experiment, select representative joint photos of each group and mark the score.

[0056] The results are as follows Figure 8 As shown in Figure a, on day 10, all CIA model mice exhibited significant redness and swelling (indicated by red arrows) and stiffness (indicated by blue arrows) in their joints, indicating successful RA model establishment. By day 18, the Ctrl group mice still showed severe redness and stiffness in their joints, with no significant improvement compared to day 10, indicating continued stability of the model lesions. The MOF group showed mild relief of redness and stiffness, suggesting that the MOF vector has a certain basic anti-inflammatory effect. The KDM group showed significant reduction in redness and swelling and a marked improvement in stiffness. The KDM@HAN group showed only mild redness and swelling, with joint appearance close to normal. By day 28, the redness and stiffness in the Ctrl group were slightly worse than before, with no sign of spontaneous recovery. The MOF group showed near-complete reduction in redness and swelling, but stiffness had not completely disappeared. The KDM group showed normal joint appearance and the stiffness had disappeared. The KDM@HAN group showed complete recovery to a healthy state, indistinguishable from normal mice. These results indicate that KDM@HAN is the most effective in alleviating joint appearance lesions. The dynamic changes in the percentage increase in thickness of the metacarpophalangeal joint of the left hind limb of mice in each group are shown in the attached figure. Figure 8As shown in Figure B. The results showed that throughout the treatment cycle, the percentage increase in claw thickness in the Ctrl group did not show a significant decreasing trend, and even exhibited slight fluctuations, indicating that RA symptoms persisted and showed no tendency to heal spontaneously. In the MOF group, the thickness decreased slowly from day 14, reaching approximately 30% by day 28, a statistically significant difference compared to the Ctrl group (P < 0.05), confirming that the MOF carrier itself has a certain anti-inflammatory effect. The KDM group showed a more significant decreasing trend, with the rate of decrease accelerating after day 18, reaching approximately 21% by day 28, demonstrating superior efficacy compared to the MOF group (P < 0.05). Of particular note, the KDM@HAN group showed a continuous and rapid decreasing trend from the start of treatment, with the percentage increase in thickness decreasing to approximately 41% by day 18 and further decreasing to approximately 9% by day 28, approaching normal levels, a significant difference compared to both the KDM and MOF groups (*P < 0.01), indicating that KDM@HAN most effectively reduced joint swelling.

[0057] Monitoring free ICG probes, ICG-loaded KDM nanoparticles (KDM@ICG), and KDM@ICG modified with HAN surface. Fluorescence signal intensity changes of the complex (KDM@ICG@HAN) in the metacarpophalangeal joint region of the right hind limb of mice. To evaluate the targeting and retention capacity of nanocarriers for ICG, we established a local inflammation model of the metacarpophalangeal joint of the left hind limb in mice. The model mice were randomly divided into three groups and administered equal doses of free ICG probes, ICG-loaded KDM nanoparticles (KDM@ICG), and HAN-modified KDM@ICG complexes (KDM@ICG@HAN) via tail vein injection, respectively. After administration, in vivo fluorescence imaging (EFI) was used to evaluate the effects of the nanocarriers on ICG targeting and retention. x / E m = 785 / 810 nm) fluorescence intensity changes in the left hind limb joint region of mice were continuously monitored at preset time points (1 d, 2 d, 4 d, 6 d, 8 d, 10 d, 12 d, 14 d). The retention effect of each group of materials in the inflamed joint site was compared.

[0058] The results are as follows Figure 9As shown, free ICG rapidly clears from the joint region, indicating that it lacks the ability to retain non-specifically in inflammatory tissue. KDM@ICG significantly extended the joint half-life of the probe to approximately 8 days, validating the passive retention (EPR) effect of the nanoparticles. The retention curve of the KDM@ICG@HAN group was the flattest. Importantly, while the free and unmodified groups showed virtually no signal on day 8, the KDM@ICG@HAN group maintained a high signal-to-noise ratio on day 12. This long-lasting retention characteristic is attributed to the active targeting adhesion function conferred by HAN modification: on the one hand, it increases cellular uptake through CD44 receptor-mediated endocytosis; on the other hand, it may promote material enrichment in the bone destruction area through the ability of ALN to actively target bone erosion sites, thus prolonging the local retention time and providing a sufficient time window for subsequent integrated diagnosis and treatment.

[0059] The scope of protection claimed by this invention is not limited to the specific embodiments described above. For those skilled in the art, this invention can have various modifications and alterations. Any modifications, improvements, and equivalent substitutions made within the concept and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A multifunctional nanocomposite based on a metal-organic framework, characterized in that, Including drug delivery systems, cartilage repair drugs, and targeted modifiers; The drug delivery carrier is a copper-zinc bimetallic organic framework, which is formed by the coordination of zinc ions, copper ions and 2-methylimidazole. The cartilage repair drug is loaded onto a drug-carrying carrier to form drug-loaded nanoparticles; The targeted modifier is a hyaluronic acid-alendronate sodium conjugate, which is modified on the surface of drug-loaded nanoparticles.

2. The multifunctional nanocomposite based on a metal-organic framework according to claim 1, characterized in that: In the copper-zinc bimetallic organic framework, the molar ratio of zinc ions to copper ions is 1:0.5~1.

5.

3. The multifunctional nanocomposite based on a metal-organic framework according to claim 1, characterized in that: The cartilage repair drug is Kartogenin.

4. The method for preparing the multifunctional nanocomposite based on the metal-organic framework according to any one of claims 1-3, characterized in that, include: Step 1: Mix a methanol solution containing zinc salt and copper salt with a methanol solution containing 2-methylimidazole and react under stirring at room temperature to obtain a copper-zinc bimetallic organic framework. Step 2: Disperse the copper-zinc bimetallic organic framework and cartilage repair drugs in ethanol and react them under stirring conditions at room temperature to obtain drug-loaded nanoparticles. Step 3: The drug-loaded nanoparticles and the hyaluronic acid-alendronate sodium conjugate are dispersed in a buffer solution and reacted under stirring conditions at room temperature to obtain the aforementioned multifunctional nanocomposite based on a metal-organic framework.

5. The method for preparing the multifunctional nanocomposite based on the metal-organic framework according to claim 5, characterized in that: In step one, the zinc salt is zinc nitrate and the copper salt is copper nitrate.

6. The method for preparing multifunctional nanocomposites based on metal-organic frameworks according to claim 4 or 5, characterized in that: In step two, the mass ratio of the copper-zinc bimetallic organic framework to the cartilage repair drug is 3-5:

1.

7. The method for preparing the multifunctional nanocomposite based on the metal-organic framework according to claim 6, characterized in that, In step three, the preparation method of the hyaluronic acid-alendronate sodium conjugate includes: adding hyaluronic acid to an aqueous solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide for activation, then adding alendronate sodium for amidation reaction, and finally purifying and drying to obtain the hyaluronic acid-alendronate sodium conjugate.

8. The method for preparing the multifunctional nanocomposite based on the metal-organic framework according to claim 7, characterized in that, The mass ratio of hyaluronic acid to sodium alendronate is 1:

2.

9. The method for preparing the multifunctional nanocomposite based on the metal-organic framework according to claim 8, characterized in that, In step three, the mass ratio of the drug-loaded nanoparticles to the hyaluronic acid-alendronate sodium conjugate is 2:

1.

10. The use of the metal-organic framework-based multifunctional nanocomposite according to any one of claims 1-3 in the preparation of a medicament for treating rheumatoid arthritis.